KORELASI KETERAMPILAN MEMBACA PEMAHAMAN BERITA DENGAN KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 3 SOLOK - Ramadhani, Taufik; Asri, Yasnur (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study is three. First, it describes the reading skills of news comprehension of VIII grade students of SMP Negeri 3 Solok. Second, describe the news text writing skills. Third, describe the correlation of reading news comprehension with news writing skills. This type of research is quantitative with descriptive methods. The design used in this study is correlational design. The population of this study was students of class VIII of SMP Negeri 3 Solok. The sample in this study was determined by proportional random sampling 15% of the population. The data of this study were in the form of scores on the reading comprehension test results of news comprehension and scores on the results of writing news text skills. This research instrument is an objective test to measure reading comprehension skills of news and performance tests to measure news text writing skills. Three results of this study. First, the reading skills of news comprehension in good qualifications (B) with an average grade of 78.56. Secondly, news writing skills in good qualifications (B) with an average of 77.78. Third, there is a correlation between reading comprehension and news writing skills with news text with n-1 degrees of freedom at a 95% confidence level. T value (3.77) is greater than t table (1.72), that is tcount> t table (3.77> 1.72), thus H0 is rejected and H1 is accepted because the test results prove that tcount is greater than t table. Kata kunci: Korelasi, Keterampilan Membaca Pemahaman Berita, Keterampilan menulis berita